Aspirin and alcohol in gastrointestinal haemorrhage. Issue 10 (October 1971) - Needham, C. D.; Kyle, J.; Jones, P. F.; Johnston, S. J.; Kerridge, D. F.
Abstract : The intake of aspirin, of alcohol, and of a combination of both, among 817 patients admitted for gastrointestinal haemorrhage is reported. The incidence of ingestion in six diagnostic groups is compared with that in two control groups. Analysis confirms that there is a markedly significant association between overt haemorrhage and the ingestion of aspirin, but this was not shown for alcohol taken alone: the combination of aspirin and alcohol showed a highly significant synergistic effect.